An insight of Facebook usage by Pakistan-based organisations: an application of netnography approach. (4th October 2022) - Ahmed, Ashir; Li, Vivien
The power of social media to engage with people and generate business value for organisations is indisputable. Although, the existing literature draws some interesting findings on the use of Facebook by small and medium enterprises (SMEs), there is a dearth of literature on the validation of such findings using Facebook metadata. This research aims to examine the various aspects of Facebook campaigns for SMEs and their effectiveness in terms of engaging with the customers. The findings of this paper are scaffold into two parts. First, it performed qualitative data analysis to understand the types of posts uploaded by the SMEs. Second, it examined the Facebook metadata to understand the types of responses, their popularity and the correlation among several types of responses. It is anticipated that the findings of this paper would help SMEs to better understand their Facebook campaigns and to better manage their Facebook campaigns in the future.